Family law reform in Indonesia according to the Maqashid al-shari’a perspective (A case study of Law no. 16 of 2019) - Roslaili, Yuni; Idris, Aisyah; Suhemi, Emi (Universitas Islam Negeri Ar-Raniry, 2021)
This research discusses family law reform in Indonesia in relation to the Law No. 16 of 2019 concerning the minimum age for child marriage. The study has been conducted using Maqashid al-syariah perspective in order to analyze first, the formulation of family law reform in Indonesia related to No. 16 of 2019, and second, the perspective of maqasid al-syariah in the law. The primary resource in this library research was Law No. 16 of 2019, and Marriage Law No. 1 of 1974. The results of the study found that family law reform regarding the age limit for marriage in Indonesia began with the existence of the judicial review process to the Constitutional Court regarding Law No.1 of 1974, more specifically Article 7 paragraph (1) which was perceived as contradictory to the 1945 Constitution Article 27 paragraph (1). This paper also proved that the determination of the age limit for marriage in Law No. 16 of 2019 is in accordance with the purpose of marriage and the objectives of sharia in general. In a nutshell, it can be concluded that there has been a reform of family law in Indonesia which can be seen from the aspect of the law regarding the age limit for marriage from nine years in the fiqh literature version to nineteen years in the version of Law No. 16 of 2019. In addition, Law no. 16 of 2019 also equates the minimum age for marriage between boys and girls, which is nineteen years, although classical fiqh literature distinguishes it.